Real-time intelligent decision support and monitoring system of critical patients - Portela, Filipe (2017)
Intensive care units are places where patients’ vital signs are continuously monitored and recorded alongside a multiplicity of clinical parameters. The main goal of this work is to study and develop an intelligent system to promote new decision-making knowledge crucial to provide better treatment to the patient. This article presents the achieved goals; in particular, the system developed for monitoring the clinical data and, using data mining technologies, for predicting clinical events with great sensitivity (90–100%), including organ failure probability, read-missions, and sepsis.